Conceptual Review On Karshya W.S.R To Protein Energy Malnutrition (PEM) In Childhood Age. - Upadhyay, Aditya Narayan; Gupta, Mahesh Narayan (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is primarily based on preventive aspect initially rather than curative. Among the Trya-upastambha (aahara,nidra,bramha-charya), aahar(diet) is considered as the first pillar. The various and common health problem can be overcome through nutritious diet. Nutritional disorder has been described in random pattern in Ayurvedic texts. Karshya (nutritional disorders) disease is familiar to under-nutrition. PEM is a type of malnutrition resulting from deficiency of protein and calories both in food over a longer period of time. Therefore, PEM is one of the diseases related to annavahasrotas(channel for transportation, digestion) The common age of incidence is usually below 5 years of age. India occupied 2nd rank after Bangladesh in the world in malnutrition of children. In Ayurvedic text, diseases such as Parigarbhika, Phakka(Rickets) , Balashosha(Marasmus) are described under karshya roga. Hence,karshya roga can be co-related to malnutrition.